MORFOMETRIK DAN SURVIVAL RATE PENGGEMUKAN KEPITING BAKAU (Scylla serrata) SISTEM APARTEMEN KEPITING DI DESA PAGARAWAN DAN PANTAI TAKARI, PULAU BANGKA - Umroh Umroh; Sudirman Adibrata; Franto Franto (Universitas Mataram, 2024)
Cultivating fattening mud crabs (Scylla serrata) usually requires a large area of land, innovation is carried out by making crab apartments. The research was conducted in September – November 2023, crab fattening locations in Pagarawan Village and Takari Beach, Bangka Regency. Location of mud crab morphometric measurements at the Aquatic Resources Management Laboratory, Bangka Belitung University. Test protein content at the DKI Jakarta Regional Health Laboratory. This research aims to examine the morphometrics, protein content and survival of mud crabs in crab apartments in Pagarawan Village and Takari Beach. Experimental research methods and community involvement to measure morphometrics, protein content and crab survival. The results of the research show that the ratio between weight, width and length of mangrove crabs in Pagarawan is 1.6:1.4:1. This shows that mud crabs are fatter. When the crab weighs around 160 grams, it is likely that the carapace width is ±14 cm and the carapace length is ±10 cm, while the crabs in Takari are smaller and thinner. The protein content of mangrove crabs in Pagarawan has an average value of 17.5 gr/100gr and in Takari 15.1 gr/100gr. The survival rate (SR) of mangrove crabs in Pagarawan is 87%. This condition means that crabs are suitable for cultivation in crab apartment boxes with a water source from a recirculation system pond. It is assumed that water pollution due to ammonia will not have much of an impact. The survival rate for mud crabs in Takari shows a zero percentage. The narrow space, food waste, and circulating water with an ammonia content of up to 0.05 mg/l are thought to have contributed to the crab's death. Water quality in both crab rearing areas shows that temperature, pH, salinity, DO, ammonia, nitrate and phosphate are still within the normal range for rearing mud crabs.